Mechanism of enhanced oral absorption of akebia saponin D by a self-nanoemulsifying drug delivery system loaded with phospholipid complex. (2nd January 2019) - Wang, Yuhui; Shen, Jinyang; Yang, Xiaolin; Jin, Ye; Yang, Zhonglin; Wang, Rufeng; Zhang, Fuming; Linhardt, Robert J.
Abstract: Akebia saponin D (ASD) exhibits a variety of pharmacological activities, such as anti-osteoporosis, neuroprotection, hepatoprotection, but has poor oral bioavailability. A self-nanoemulsifying drug delivery system loaded with akebia saponin D - phospholipid complex (APC-SNEDDS) (composition: Peceol: Cremophor ® EL: Transcutol HP: ASD: phospholipid; ratio: 10:45:45:51:12.3, w:w:w:w:w) was first developed to improve the oral absorption of saponins and it was found to significantly enhance ASD's oral bioavailability by 4.3 - fold ( p  < .01). This study was conducted to elucidate the mechanism of enhanced oral absorption of ASD by the drug delivery system of APC-SNEDDS. The aggregation morphology and particle size of ASD and APC-SNEDDS prepared in aqueous solutions were determined by transmission electron microscope and particle size analyzer, respectively. Stability of ASD and APC-SNEDDS in gastrointestinal luminal contents and mucosa homogenates were also explored. The differences of in situ intestinal permeability of ASD and APC-SNEDDS were compared. APC-SNEDDS reduced the aggregation size from 389 ± 7 nm (ASD) to 148 ± 3 nm (APC-SNEDDS). APC-SNEDDS increased the remaining drug in large intestine luminal contents from 47 ± 1% (ASD) to 83 ± 1% (APC-SNEDDS) during 4 h incubation. APC-SNEDDS provided an 11-fold increase in K a value and an 11-fold increase in P eff value compared to ASD. In summary, APC-SNEDDS improved ASD's oral bioavailability mainly by increasing membrane permeability, destroying self-micelles and inhibiting the intestinal metabolism.